Stenting in posterior inferior cerebellar artery aneurysm: a case report - Anggia, Amelia; Muda, Ahmad Sobri; Tharek, Anas; Kamis, Mohd Fandi Al Khafiz; Shamsuddin Perisamy, Rajeev; Siow, Li Ting; Idris, Badrisyah (Longe Medikal Sdn Bhd, 2024)
Posterior inferior cerebellar artery (PICA) distal aneurysm is a relatively rare condition, accounting for 1% or less of all cerebral aneurysms. They may manifest as severe headaches, altered consciousness, lower cranial nerve dysfunction, brainstem compression, or posterior fossa symptoms such as nausea, vomiting, imbalance, or ataxia. Digital Subtraction Angiography (DSA) is the gold standard for detecting aneurysmal SAH. Endovascular treatment (EVT) has become the primary strategy for managing PICA aneurysms in recent years.